Biodistribution of boron after intravenous 4-dihydroxyborylphenylalanine-fructose (BPA-F) infusion in meningioma and schwannoma patients: A feasibility study for boron neutron capture therapy. (December 2015) - Kulvik, Martti; Kallio, Merja; Laakso, Juha; Vähätalo, Jyrki; Hermans, Raine; Järviluoma, Eija; Paetau, Anders; Rasilainen, Merja; Ruokonen, Inkeri; Seppälä, Matti; Jääskeläinen, Juha
Abstract: We studied the uptake of boron after 100 mg/kg BPA infusion in three meningioma and five schwannoma patients as a pre-BNCT feasibility study. With average tumour-to-whole blood boron concentrations of 2.5, we discuss why BNCT could, and probably should, be developed to treat severe forms of the studied tumours. However, analysing 72 tumour and 250 blood samples yielded another finding: the plasma-to-whole blood boron concentrations varied with time, suggesting that the assumed constant boron ratio of 1:1 between normal brain tissue and whole blood deserves re-assessment. Highlights: Boron biodistribution in NF2, schwannoma and meningioma patients. BNCT seems to be feasible also for meningioma, schwannoma and NF2 patients. Mean tumour to blood boron level ratio from 320 samples was 3.8, with SD of 1.5 and range from 1.0 to 6.8.